A Meta-Analysis on Students' Social Collaborative Knowledge Construction using Flipped Classroom Model - Wen, A. S. (Institute of Electrical and Electronics Engineers Inc., 2016)
The purpose of this paper is to identify the major ICT skills and learning strategies involved Social Collaborative Knowledge Construction using Flipped Classroom Model. The approach adopted in this article is a Meta-Analysis on Students' Social Collaborative Knowledge Construction using Flipped Classroom Model. Social Collaborative Knowledge Construction (SCKC) process involves peer to peer communication which help students to understand, investigate, and determine how the implicit cultural assumptions, frames of references, perspectives, and biases within a discipline influence the ways in which knowledge is constructed within it. Flipped Classroom Model (FCM) turns learning by replacing traditional classroom lectures with video tutorials that students need to watch before lesson time. Students do their homework or assignments with the help of instructor during class time. FCM can be a solution to contribute to the SCKC process. The paper presents the major ICT skills (creativity skill, problem solving skill and critical thinking skill) and explores the trend of learning strategies used in FCM that could be used for future research. This paper discusses the benefits, potentials and challenges of Students' SCKC using FCM.